PENGEMBANGAN INSTRUMEN PEMETAAN AWAL LITERASI DAN NUMERASI ANAK USIA DINI - Laksana, Dek Ngurah Laba; Ita, Efrida; Ngura, Elisabeth Tantiana; Saju, Cresensiana Florentina (Universitas Pendidikan Ganesha, 2023)
Understanding the early childhood mapping resources that are now available so that educators can assess students' literacy and numeracy It makes it challenging for teachers to assess how well their students are reading and using numbers. The aim of this research is to create early mapping tools for children's literacy and numeracy skills and to determine the instruments' levels of worth. The R&D 3D model (define, design, and extent) is used in this research technique. Two academics who served as the instrument's validators are the source of the data used in this investigation. A questionnaire is used in the data collection process. Techniques for analysing data that use Cronbach alpha for instrument reliability and validity tests. According to research, coefficiencies of application for a high-category early child literacy instrument are obtained by using the Gregory formula to the results of expert validation for early childhood literacy instruments. These yields coefficients of content. According to preliminary literacy instrument test findings, every item is valid. With a score of 0.933, Cronbach's alpha falls into the highly reliable category. Early evaluations of early childhood numerical instruments indicated a very high content. All qualifying items in the reliability testing of numerating instruments have a Cronbach's alpha score of 0.914, bringing them in a highly reliable category. Based on these results, the instrument can be used to assess early childhood development through assessing abilities in numeracy and literacy.